2017
DOI: 10.1016/j.ceramint.2017.01.079
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional change behavior of porous MgTi 2 O 5 in reactive sintering

Abstract: Volume-shrinkage of a sample in reactive sintering generally tends to be larger than that in conventional sintering. New techniques to suppress the volume shrinkage are eagerly needed for actual manufacturing. Recently, we have reported that reactively sintered porous MgTi2O5 from hydromagnesite and TiO2 rutile showed less volume shrinkage than that from hydromagnesite and TiO2 anatase. The result demonstrated that the compositional control of starting polymorphs can be a potential technique to optimize the vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…6) that some SPGs by furnace heating (not by the in situ observation) had the diameter of ~150 m, which implies the size shrinkage under the slower heating rate became milder. Formation of the 3-D network structure may result in such mild shrinkage (or even expansion) during the heating [24].…”
Section: Size Control Of Spgsmentioning
confidence: 99%
“…It was reported that the partial replacement of Mg by B 2+ (B 2+ = Co, Ni, and Zn) increases the structural densification and upgrades the dielectric performance of MgTiO 3 . (Mg 0.95 B 2+ 0.05 )TiO 3 with an ilmenite-type structure has been documented to possess excellent dielectric performance [8,13,14] [22][23][24][25][26][27]. In this paper, with partial substitution of Mg 2+ (0.072 nm) by Ni 2+ (0.069 nm), the microstructure densification of (Mg 0.6 Zn 0.4 ) 0.95 Ni 0.05 TiO 3 was observed, and microwave dielectric performance of that was also further improved compared to (Mg 0.6 Zn 0.4 )TiO 3 .…”
Section: Introductionmentioning
confidence: 99%